PRDM16 regulates arterial development and vascular integrity - Thompson, Michael; Sakabe, Masahide; Verba, Mark; Hao, Jiukuan; Meadows, Stryder M.; Lu, Q. Richard; Xin, Mei (Frontiers in Physiology, 2023)
Proper vascular formation is regulated by multiple signaling pathways. The vascular endothelial growth factor (VEGF) signaling promotes endothelial proliferation. Notch and its downstream targets act to lead endothelial cells toward an arterial fate through regulation of arterial gene expression. However, the mechanisms of how endothelial cells (ECs) in the artery maintain their arterial characteristics remain unclear. Here, we show that PRDM16 (positive regulatory domain-containing protein 16), a zinc finger transcription factor, is expressed in arterial ECs, but not venous ECs in developing embryos and neonatal retinas. Endothelial-specific deletion of Prdm16 induced ectopic venous marker expression in the arterial ECs and reduced vascular smooth muscle cell (vSMC) recruitment around arteries. Whole-genome transcriptome analysis using isolated brain ECs show that the expression of Angpt2 (encoding ANGIOPOIETIN2, which inhibits vSMC recruitment) is upregulated in the Prdm16 knockout ECs. Conversely, forced expression of PRDM16 in venous ECs is sufficient to induce arterial gene expression and repress the ANGPT2 level. Together, these results reveal an arterial cell-autonomous function for PRDM16 in suppressing venous characteristics in arterial ECs.